Enhancing Qur'an Reading Proficiency in Madrasahs Through Teaching Strategies - Basir, Abd.; Tamjidnor, Tamjidnor; Suraijiah, Suraijiah; Karoso, Subianto; Saidi, Suid; Sholihah, Maidatus (Universitas Pesantren Kh Abdul Chalim Mojokerto, 2024)
This study investigates the teaching strategies implemented at Madrasah Ibtidaiyah Negeri 3 Banjarmasin to enhance students' ability to read the Qur'an. Employing a qualitative research approach, the study utilizes descriptive methods to analyze how these strategies are executed within the classroom setting. Primary data were gathered through structured observations and in-depth teacher interviews, supplemented by a literature review to contrast current findings with established pedagogical practices. This comprehensive approach aimed to provide a nuanced understanding of the instructional methodologies, their implementation, and the contextual factors affecting their efficacy. The findings indicate combining traditional and contemporary teaching strategies significantly improves students' Qur'anic reading abilities. Repetitive recitation and group readings are pivotal in fostering phonetic skills and memorization. At the same time, incorporating digital tools and visual aids enhances engagement and aids in understanding complex Tajweed rules. Role-playing exercises have also proven to boost students' confidence and interactive learning. However, challenges such as inconsistent student engagement levels, limited technological resources, and large class sizes have been identified as substantial obstacles. These issues highlight the need for continued institutional support and resource allocation to optimize the effectiveness of teaching strategies and ensure comprehensive learning outcomes for all students.